FRI0129 Assessing the Economic Impact of Comprehensive Disease Control on Total Direct Medical Expenditures for Rheumatoid Arthritis. (9th June 2015) - Emery, P.; Kavanaugh, A.; Bao, Y.; Betts, K.A.; Macalalad, A.R.; Lin, P.; Galebach, P.; Garg, V.
Abstract : Background: Comprehensive disease control (CDC) of Rheumatoid Arthritis (RA) is simultaneous achievement of clinical remission (Disease Activity Score [DAS28]<2.6), normal physical functioning (Health Assessment Questionnaire Disability Index [HAQ-DI]<0.5), and radiographic non-progression (modified Total Sharp Score [ΔmTSS]≤0.5). CDC has been linked to clinical benefits including improvements in quality of life (QoL) and reductions in pain and fatigue, but its economic impact has not been quantified. 1 Objectives: To quantify the impact of CDC achievement on direct medical expenditures from a US third party payer perspective and compare the medical expenditures of CDC achievers to the medical expenditures of CDC non-achievers, including patients who achieve other disease control targets. Methods: This study used data from the 2011 Medical Expenditure Panel Survey (MEPS) Household Component, and the PREMIER and DE-019 randomized controlled trials. Adult RA patients with complete SF-12 physical (PCS) and mental (MCS) component scores were selected from the MEPS data. The annual direct medical expenditures of these patients were modeled as a function of PCS, MCS, and patient characteristics (age, sex, race, disease duration, obesity, and comorbidities). MEPS estimates were adjusted with survey weights to make them nationally representative. A log transformation was applied due to the non-normality of the cost data. Using the PREMIER and DE-019 clinical trial data, annual direct medical expenditures were estimated using the MEPS model and compared between CDC achievers and non-achievers (including those who achieved HAQ-DI<0.5, DAS28<2.6, ΔmTSS≤0.5, or Clinical Disease Activity Index [CDAI] remission without achieving CDC). Results: A total of 498 RA patients (representative of the US RA population) from MEPS were identified. After adjusting for patient characteristics, each 1-point increase in PCS and MCS were associated with total medical expenditure reductions of 3% and 1%, respectively. In the clinical trial data, patients who achieved CDC were estimated to have approximately half the mean total annual costs compared with those not achieving CDC (2, 078 v. 3, 923, p<0.001). CDC achievers also had significantly lower (p<0.001) costs than patients who achieved HAQ-DI<0.5 (2, 409), DAS28<2.6 (2, 690), or ΔmTSS≤0.5 (3, 605) but not CDC. The patients who achieved both CDC and CDAI remission had significantly lower costs than the patients who only achieved CDAI remission (1, 923 v. 2, 368, p<0.001). Conclusions: RA patients who achieve CDC have significantly lower annual direct medical costs compared with CDC non-achievers, including patients who achieve other disease control targets. CDC is an important treatment goal from the patient perspective, as well as one that provides economic value to US third party payers. References: Emery, P., Kavanaugh, A., Bao, Y., Ganguli, A. & Mulani, P. Comprehensive disease control (CDC): what does achieving CDC mean for patients with rheumatoid arthritis? Annals of the rheumatic diseases, doi:10.1136/annrheumdis-2014-205302 (2014). Disclosure of Interest: P. Emery Consultant for: AbbVie, Bristol-Myers Squibb, Merck, Novartis, Pfizer Inc, Roche-Chugai, UCB Pharma Ltd., A. Kavanaugh Consultant for: Roche, AbbVie, Amgen, UCB, BMS, Pfizer, Janssen, Y. Bao Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., K. Betts Employee of: Analysis Group Inc., A. Macalalad Employee of: Analysis Group Inc., P. Lin Employee of: Analysis Group Inc., P. Galebach Employee of: Analysis Group Inc., V. Garg Shareholder of: AbbVie Inc., Employee of: AbbVie Inc.